PO087 Research participants are not representative of the population age distribution of pd. (1st December 2017) - Macleod, Angus; Henery, Rachel; Nwajiugo, Paul; Counsell, Carl
Abstract : Background: Most sources state the mean age at onset in Parkinson's disease (PD) to be 60. We aimed to compare the distribution of the age at onset in population-based incidence studies with the age of onset in published studies in PD. Methods: We systematically reviewed all incidence studies in PD. We extracted the mean age at onset (or diagnosis). We performed random-effects meta-analysis of mean age at inception (i.e., either onset or diagnosis). We reviewed the mean age at onset in all research studies in PD published over six months in Movement Disorders (July to September 2016), and compared this to the pooled mean age at inception from the identified incidence studies Results: Twelve incidence studies reported mean age at inception in PD. Pooled mean age was 69.3 (95% CI 67.0–71.7) with major heterogeneity (I 2 =96.8%). Of 41 studies published in Movement Disorders during the stated time period, 31 published the mean age at onset with mean mean age at onset of 59.1. Conclusions: The mean age at onset in PD is is about ten years older than the mean age at onset in research participants. Further research should assess the influence of this selection bias on research findings.